2021
DOI: 10.2196/24590
|View full text |Cite
|
Sign up to set email alerts
|

Commencement of and Retention in Web-Based Interventions and Response to Prompts and Reminders: Longitudinal Observational Study Based on Two Randomized Controlled Trials

Abstract: Background Web-based interventions are effective for several psychological problems. However, recruitment, adherence, and missing data are challenges when evaluating these interventions. Objective This study aimed to describe the use patterns during the commencement phase, possible retention patterns (continuation of data provision), and responses to prompts and reminders among participants in 2 randomized controlled trials (RCTs) evaluating web-based i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Although participants agreed to complete the program modules as part of this RCT, completion was not mandatory, and all participants had the option to drop out, withdraw, or, if so inclined, simply not view the content while it was running. In viewing RealConsent completion rates, our results show that 75.5% (335/444) of the participants completed all 4 modules of the program, which can be viewed as a high percentage of completion for a web-based program [ 67 ] and which suggests perceived relevance and quality. Further research regarding the acceptability of RealConsent and its relevance and perceived quality in terms of entertainment value is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although participants agreed to complete the program modules as part of this RCT, completion was not mandatory, and all participants had the option to drop out, withdraw, or, if so inclined, simply not view the content while it was running. In viewing RealConsent completion rates, our results show that 75.5% (335/444) of the participants completed all 4 modules of the program, which can be viewed as a high percentage of completion for a web-based program [ 67 ] and which suggests perceived relevance and quality. Further research regarding the acceptability of RealConsent and its relevance and perceived quality in terms of entertainment value is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although it was not extreme, we experienced some loss to follow-up in terms of completion of the respective web-based programs and follow-up survey. It is unclear what the potential reasons were for this loss to follow-up; however, previous research has shown that attrition in web-based trials may be higher than that in in-person trials [ 67 , 69 , 70 ]. Nevertheless, our observed attrition rates (overall 161/881, 18.3%) are lower than (eg, 40% [ 71 ]), or in line with (eg, 18% [ 72 ]), other in-person SV risk reduction trials with similar follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Although the fortnightly recovery check-in phone calls are intended to enhance retention of participants in the BFO arm of the study, it may be more challenging to retain participants in the study once the treatment period is over and they are no longer receiving the check-in phone calls—a prediction supported by previous systematic reviews into smoking cessation interventions [ 51 ]. Every attempt will be made to obtain follow-up data—as follow-up data is being collected via electronic methods, there is scope to send reminders to participants to complete follow-up assessments via email, a method indicated to be successful in increasing follow-up retention in previously conducted RCTs [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, subjective task performance in the MDT-OS was rated lower and retention was shorter compared to ORR and CSR. This might suggest that specific feedback strategies to increase subjective task performance levels might help to increase long term retention ( 23 ). Of note, Pratap and colleagues report that retention times are in general higher in studies with personal contact between participants and study personnel.…”
Section: Discussionmentioning
confidence: 99%